Highly acidic pH facilitates enamel protein self-assembly, apatite crystal growth and enamel protein interactions in the early enamel matrix - Zhang, Youbin; Jin, Tianquan; Zhu, Weiying; Pandya, Mirali; Gopinathan, Gokul; Allen, Michael; Reed, David; Keiderling, Timothy; Liao, Xiubei; Diekwisch, Thomas G. H. (Frontiers in Physiology, 2022)
Tooth enamel develops within a pH sensitive amelogenin-rich protein matrix. The purpose of the present study is to shed light on the intimate relationship between enamel matrix pH, enamel protein self-assembly, and enamel crystal growth during early amelogenesis. Universal indicator dye staining revealed highly acidic pH values (pH 3–4) at the exocytosis site of secretory ameloblasts. When increasing the pH of an amelogenin solution from pH 5 to pH 7, there was a gradual increase in subunit compartment size from 2 nm diameter subunits at pH 5 to a stretched configuration at pH6 and to 20 nm subunits at pH 7. HSQC NMR spectra revealed that the formation of the insoluble amelogenin self-assembly structure at pH6 was critically mediated by at least seven of the 11 histidine residues of the amelogenin coil domain (AA 46–117). Comparing calcium crystal growth on polystyrene plates, crystal length was more than 20-fold elevated at pH 4 when compared to crystals grown at pH 6 or pH 7. To illustrate the effect of pH on enamel protein self-assembly at the site of initial enamel formation, molar teeth were immersed in phosphate buffer at pH4 and pH7, resulting in the formation of intricate berry tree-like assemblies surrounding initial enamel crystal assemblies at pH4 that were not evident at pH7 nor in citrate buffer. Amelogenin and ameloblastin enamel proteins interacted at the secretory ameloblast pole and in the initial enamel layer, and co-immunoprecipitation studies revealed that this amelogenin/ameloblastin interaction preferentially takes place at pH 4—pH 4.5. Together, these studies highlight the highly acidic pH of the very early enamel matrix as an essential contributing factor for enamel protein structure and self-assembly, apatite crystal growth, and enamel protein interactions.